Good Governance Between Goverment and Society in Developing Pangkalan pendaratan Ikan (PPI) (The Study on Pangkalan Pendaratan Ikan Popoh Beach, Tulungagung) - Novi Arinda Kusumawati (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
With the existence of local autonomy, so local goverment have authority to regulate his own area, local regulation No 27 Tahun 2010 about â€œmanaging coast area and litle islan oriented in society. the potential ofÂ Tulungagung and local regulation that made facilitate government manage and develop PPI Popoh that aimed for welfare community around and improve economy in this area. In this research, researcher use qualitative descriptive type research as analysis to know role of government and internal society PPI Popoh development as well as restricting factor and supporter in PPI Popoh development. In PPI Popoh development government have corporation with society to facilitate in process development as well as in this development area. Government make the function as facilitators, policy maker, stability, mediataor and dynamist. So the society able to keep rights it protected, impact policy that made by government as well as develop resource human, means of communication inter member community. Cooperation among government and community provide impact that is good in PPI development. Accountabilitas, transparency and participation by government as well as by PPI Popoh community creates PPI Popoh more develop In the development PPI Popoh has factor supporter as well as inhibitory factor like facility and infrastructure that not yet fulfilled, lack of employee. Supporting factors like stategis PPI Popoh location facilitates rationing fish and PPI Popoh area that border on place tourism. Keywords: Good Goverment, Local Autonomy